2022
DOI: 10.3892/br.2022.1510
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration and convergent factors contributing to the deterioration of the cytoskeleton in Alzheimer's disease, cerebral ischemia and multiple sclerosis (Review)

Abstract: The cytoskeleton is the main intracellular structure that determines the morphology of neurons and maintains their integrity. Therefore, disruption of its structure and function may underlie several neurodegenerative diseases. This review summarizes the current literature on the tau protein, microtubule-associated protein 2 (MAP2) and neurofilaments as common denominators in pathological conditions such as Alzheimer's disease (AD), cerebral ischemia, and multiple sclerosis (MS). Insights obtained from experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 110 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…This observation was consistent with a dramatic reduction of fibroblast-like cells in the LMD pia enumerated using scRNAseq (66% of all cells in healthy pia versus 3% of all cells in LMD, Supplemental Figure 10B ). Previously, neurological degeneration was associated with a loss of cortical microtubule-associated protein 2 (MAP2) reactivity and gliosis marked by an increase in GFAP expression in schizophrenia, Parkinson’s disease, Alzheimer’s disease, and other neurodegenerative processes 71,72 . We also observed a loss of MAP2 reactivity in the cortex of animals with LMD ( Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…This observation was consistent with a dramatic reduction of fibroblast-like cells in the LMD pia enumerated using scRNAseq (66% of all cells in healthy pia versus 3% of all cells in LMD, Supplemental Figure 10B ). Previously, neurological degeneration was associated with a loss of cortical microtubule-associated protein 2 (MAP2) reactivity and gliosis marked by an increase in GFAP expression in schizophrenia, Parkinson’s disease, Alzheimer’s disease, and other neurodegenerative processes 71,72 . We also observed a loss of MAP2 reactivity in the cortex of animals with LMD ( Figure 6F ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, β-Tubulin III staining allowed us to observe other relevant neurodegenerative processes such as disorganization in the layers of the brain cortex, the presence of cortical dark neurons, and alterations in cortical and hippocampal neural processes and length of neuronal prolongations, as a consequence of impairments in the neuronal cytoskeleton. The cytoskeleton is the main intracellular structure that determines the morphology of neurons and maintains their integrity and, thus, disruption of its structure and function may underlie several neurodegenerative processes [ 28 ]. Therefore, we confirmed an age-related state of neurodegeneration in our animal model of ageing, as had already observed in previous studies [ 11 , 12 , 13 , 18 , 19 , 20 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[71][72][73][74][75][76][77] Regulators of the cytoskeleton such as cofilin, RhoA/ROCK pathway components, MAPs, GSK3β have emerged as potential therapeutic targets for treating this dysregulation. 74,[77][78][79][80][81] It has previously been shown that F-actin levels are reduced in SCA1 and SCA3 model class IV da neurons. 35 Our results suggest that this reduction can be ameliorated by activating dendrite regeneration mechanisms via single branch injury.…”
Section: The Cytoskeleton In Regeneration and Neurodegenerative Diseasementioning
confidence: 99%